Optimizing photocatalysts and photoreactors for solar fuel synthesis - Kant, Paul Philipp (KIT Scientific Publishing, 2023)
The work represents a toolbox for the design of a highly efficient photocatalytic process for solar-driven synthesis. The focus is the optimization of photoreactors and photocatalysts. The described photoreactor design strategy is based on numerical methods mapping radiation transport and additive manufacturing delivering prototypes. The photocatalyst engineering is based on suitable photocatalyst support strategies and a method for the determination of the quantum yield in photoreactions.